Peran Perempuan di Desa Wisata Kampung Ulos Huta Raja terhadap Pariwisata Berkelanjutan - Erfina Yanti Pasaribu; Apriliani Lase (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Women's empowerment is one of the crucial aspects that needs to be considered in the community empowerment stage. This study focuses on the role of women in the Ulos Hutaraja Tourism Village in supporting sustainable tourism development. The research method used a descriptive qualitative approach with interview, observation, and documentation techniques. The results show that women's contributions can be seen through three main dimensions. First, the economic dimension, where women are able to increase family income while opening new business opportunities for the community. Second, the social dimension, where women's involvement in tourism activities strengthens solidarity, cooperation, and the active role of the community in maintaining the environment of the tourism village. Third, the cultural dimension, where women are the main actors in preserving the tradition of ulos weaving, which is the identity and main attraction of tourism in Ulos Hutaraja Village. However, the study also found several obstacles faced by women, such as limited business capital, managerial skills, digital promotion, and access to a wider market network. Therefore, support is needed from various parties, including the government, educational institutions, and tourism industry players, to provide training, mentoring, and supporting facilities. With this strengthening, women's role will not only focus on economic improvement, but also be able to realize sustainable tourism development that maintains a balance between economic, social, cultural, and environmental aspects.